2018
DOI: 10.1021/acsnano.8b07807
|View full text |Cite
|
Sign up to set email alerts
|

Single Au Atom Doping of Silver Nanoclusters

Abstract: Ag29 nanoclusters capped with lipoic acid (LA) can be doped with Au. The doped clusters show enhanced stability and increased luminescence efficiency. We attribute the higher quantum yield to an increase in the rate of radiative decay. With mass spectrometry, the Au-doped clusters were found to consist predominantly of Au1Ag28(LA)123–. The clusters were characterized using X-ray absorption spectroscopy at the Au L3-edge. Both the extended absorption fine structure (EXAFS) and the near edge structure (XANES) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 71 publications
(181 reference statements)
0
53
1
Order By: Relevance
“…For the counterions of these [Ag 29 (SSR) 12 (PPh 3 ) 4 ] 3À nanoclusters, the Ag 29 -Na 1 nanocluster comprised three NMPconjoined [Na 1 (NMP) 5 ] + cations per Ag 29 compound ( Fig. 1A and B), whereas each Ag 29 compound matched only one DMFconjoined [Na 3 (DMF) 12 ] 3+ cation in the structure of Ag 29 -Na 3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the counterions of these [Ag 29 (SSR) 12 (PPh 3 ) 4 ] 3À nanoclusters, the Ag 29 -Na 1 nanocluster comprised three NMPconjoined [Na 1 (NMP) 5 ] + cations per Ag 29 compound ( Fig. 1A and B), whereas each Ag 29 compound matched only one DMFconjoined [Na 3 (DMF) 12 ] 3+ cation in the structure of Ag 29 -Na 3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal lattice of Ag 29 -Na 1 contained six [Ag 29 (SSR) 12 (-PPh 3 ) 4 ] 3À anions and 18 [Na 1 (NMP) 5 ] + cations (Fig. 1E); by comparison, two [Ag 29 (SSR) 12 (PPh 3 ) 4 ] 3À anions and two [Na 3 (DMF) 12 ] 3+ cations were observed in the unit cell of Ag 29 -Na 3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, X‐ray absorption fine structure (XANFS) is known for accurately reflecting the oscillatory structure of the samples according to the X‐ray absorption coefficient . It generally includes X‐ray absorption near edge structure (XANES) and extended X‐ray absorption fine structure (EXAFS).…”
Section: Fabrication Strategies and Characteristic Methods Of Sagmentioning
confidence: 99%
“…It has been demonstrated that alloying can effectively enhance the stability and materials performance (e.g., luminescence 154 and catalytic activity 99,105,155 ) of metal NCs. In addition to the well-known co-reduction method, the alloying can be achieved at atomic precision through reactions of the preformed metal NCs with various heteroatom sources, including metal cations, 53 M(I)-SR/M(II)-SR complexes, metal NCs, and metal surfaces.…”
Section: Molecular Interactions/reactions In Alloying Of Metal Ncsmentioning
confidence: 99%